The reliability and validity of the Thai version of Visual Cognitive Assessment Test (VCAT:Th ) - Juntorn, Sutinun; Wangkawan, Thitiya; Phatcharapisitgul, Parlinzhaadaa; Thichanpiang, Peeradech; Rodkaeo, Tharadon; Sangsawee, Paweena (Journal of Associated Medical Sciences, 2025)
Background: The global prevalence of dementia is projected to nearly double every 20 years, significantly impacting the quality of life for both individuals with dementia and their caregivers. Early detection is therefore critical, particularly in the context of Thailand’s rapidly aging population. The Visual Cognitive Assessment Test (VCAT) is a visual-based cognitive screening tool designed to overcome educational limitations commonly associated with traditional assessments. Widely adopted across Southeast Asia, the VCAT demonstrates high sensitivity in detecting cognitive impairments from the earliest stages. Objectives: This study aims to evaluate the validity and reliability of the Thai version of the Visual Cognitive Assessment (VCAT: Th) Materials and methods: This study employed a cross-sectional, psychometric design and included 98 participants, consisting of 31 healthy controls (HC), 31 individuals with mild cognitive impairment (MCI), and 36 individuals with mild Alzheimer’s disease (AD). The HC group was recruited from community-dwelling individuals residing in Bangkok and its surrounding metropolitan areas, while the MCI and mild AD groups were recruited from the Faculty of Medicine Ramathibodi Hospital, Mahidol University. All participants completed the Thai version of the Visual Cognitive Assessment Test (VCAT: Th), which was culturally adapted from the original version to suit the Thai context. The collected data was then used to evaluate internal consistency, test–retest reliability, concurrent validity, and known-group validity. Results: The VCAT: Th demonstrated strong psychometric properties. Internal consistency was highly acceptable (α=0.78), and test-retest reliability was excellent (ICC=0.95). Concurrent validity showed a strong and significant correlation with MoCA scores (r=0.79,p<0.001). Known-group validity revealed significant group differences with a large effect size (η²=0.53). Conclusion: The VCAT: Th is a culturally adapted cognitive assessment tool that effectively identifies impairments typically present in the early stages of cognitive decline. It demonstrates acceptable psychometric properties and is appropriate for use within the Thai population.